2009
DOI: 10.1136/gut.2008.152652
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box M1B is a determinant of rat susceptibility to hepatocarcinogenesis and sustains ERK activity in human HCC

Abstract: Forkhead box M1B is a determinant of rat susceptibility to hepatocarcinogenesis and sustains ERK activity in human HCC ABSTRACT Background and aim: Previous studies indicate unrestrained cell cycle progression in liver lesions from hepatocarcinogenesis-susceptible Fisher 344 (F344) rats and a block of G 1 -S transition in corresponding lesions from resistant Brown Norway (BN) rats. Here, the role of the Forkhead box M1B (FOXM1) gene during hepatocarcinogenesis in both rat models and human hepatocellular carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 46 publications
6
69
1
Order By: Relevance
“…therefore, validity of the prognostic value of FoXM1 expression could be at least helpful to identify those patients who would benefit from closer monitoring and from improved treatment strategies. previous studies demonstrated that FoXM1 expression was inversely associated with survival of Hcc patients (18). In line with the current data, we found that expression of FoXM1 was a strong independent predictor of os for Hcc patients.…”
Section: Foxm1 Expression ----------------------supporting
confidence: 92%
See 2 more Smart Citations
“…therefore, validity of the prognostic value of FoXM1 expression could be at least helpful to identify those patients who would benefit from closer monitoring and from improved treatment strategies. previous studies demonstrated that FoXM1 expression was inversely associated with survival of Hcc patients (18). In line with the current data, we found that expression of FoXM1 was a strong independent predictor of os for Hcc patients.…”
Section: Foxm1 Expression ----------------------supporting
confidence: 92%
“…this association strongly suggests that FoXM1 could be further evaluated as a biomarker to identify subsets of Hcc tumors with aggressive phenotype. nevertheless, a recent study has documented discrepant data that no significant correlation was observed between FoXM1 expression and clinicopathological parameters in 58 western Hcc patients (18). possible explanations for this discrepancy include differences in detection method for FoXM1 protein, cohort size and patient population between that and our studies.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…FoxM1 has been shown to activate the oncogenic pathways that are important in carcinogenesis such as mitogen activated protein kinase (MAPK), extracellular signal-regulated kinase (ERK), phosphatdyl inositol 3-kinase (PI3k)/Akt), nuclear factor kappa-B and sonic hedgehog (SHH) [33][34][35][36][37]. Moreover, FoxM1 has been shown to decrease the gene expression levels of the tumor suppressor genes and also the genes involved in cellular senescence like p53 and p21 cip1 [20,38].…”
Section: Discussionmentioning
confidence: 99%
“…The data above indicate that FoxM1 is a potential specific target for HCC therapy. Interestingly, a recent study showed that lower expression of FoxM1 in HCC was associated with prolonged disease-free survival after curative liver resection and validated FoxM1 as a prognostic marker for HCC [15] .…”
Section: Discussionmentioning
confidence: 99%